Genome-Wide Identification of TCP Family Transcription Factors in Medicago truncatula Reveals Significant Roles of miR319-Targeted TCPs in Nodule Development - Wang, Hongfeng; Wang, Hongwei; Liu, Rong; Xu, Yiteng; Lu, Zhichao; Zhou, Chuanen (Frontiers in Plant Science, 2018)
TCP proteins, the plant-specific transcription factors, are involved in the regulation of multiple aspects of plant development among different species, such as leaf development, branching, and flower symmetry. However, thus far, the roles of TCPs in legume, especially in nodulation are still not clear. In this study, a genome-wide analysis of TCP genes was carried out to discover their evolution and function in Medicago truncatula. In total, 21 MtTCPs were identified and classified into class I and class II, and the class II MtTCPs were further divided into two subclasses, CIN and CYC/TB1. The expression profiles of MtTCPs are dramatically different. The universal expression of class I MtTCPs was detected in all organs. However, the MtTCPs in CIN subclass were highly expressed in leaf and most of the members in CYC/TB1 subclass were highly expressed in flower. Such organ-specific expression patterns of MtTCPs suggest their different roles in plant development. In addition, most MtTCPs were down-regulated during the nodule development, except for the putative MtmiR319 targets, MtTCP3, MtTCP4, and MtTCP10A. Overexpression of MtmiR319A significantly reduced the expression level of MtTCP3/4/10A/10B and resulted in the decreased nodule number, indicating the important roles of MtmiR319-targeted MtTCPs in nodulation. Taken together, this study systematically analyzes the MtTCP gene family at a genome-wide level and their possible functions in nodulation, which lay the basis for further explorations of MtmiR319/MtTCPs module in association with nodule development in M. truncatula.